A prospective observational post‐marketing study of natalizumab‐treated multiple sclerosis patients: clinical, radiological and biological features and adverse events. The BIONAT cohort. (12th June 2013) - Outteryck, O.; Ongagna, J.C.; Brochet, B.; Rumbach, L.; Lebrun‐Frenay, C.; Debouverie, M.; Zéphir, H.; Ouallet, J.C.; Berger, E.; Cohen, M.; Pittion, S.; Laplaud, D.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose BIONAT is a French multicentric phase IV study of natalizumab (NTZ)‐treated relapsing−remitting multiple sclerosis (MS) patients. The purpose of this study was to collect clinical, radiological and biological data on 1204 patients starting NTZ, and to evaluate the clinical/radiological response to NTZ after 2 years of treatment. Methods Patients starting NTZ at 18 French MS centres since June 2007 were included. Good response to NTZ was defined by the absence of clinical and radiological activity. Data analysed in this first report on the BIONAT study focus on patients who started NTZ at least 2 years ago (n = 793; BIONAT2Y). Results NTZ was discontinued in 17.78% of BIONAT2Y. The proportion of patients without combined disease activity was 45.59% during the first two successive years of treatment. Systematic dosage of anti‐NTZantibodies (Abs) detected only two supplementary patients with anti‐NTZ Abs compared with strict application of recommendations. A significant decrease of IgG, M concentrations at 2 years of treatment was found. Conclusions The efficacy of NTZ therapy on relapsing−remitting MS in a real life setting is confirmed in the BIONAT cohort. The next step will be the identification of biomarkers predicting response to NTZ therapy and adverse events.